Energy-Efficient Clustering and Routing Protocols in Wireless Sensor Network: A Survey - Karthik, M; Mohanapriya, S (International Journal of Computer Sciences and Engineering, 2020)
Wireless Sensor Network (WSN) has increased the interest of researchers in several challenging characteristics. The most vital challenge in these networks is energy minimization. One of the most accepted solutions in constructing the energyefficient WSN is to cluster the networks. In clustering, the nodes are split into some clusters and few nodes are elected to be cluster heads. In a clustered WSN, the normal nodes can transmit their sensed data to the cluster head. Then, the cluster head can aggregate and transmit those data to the base station. Typically, clustering involves different merits such as scalability, energy-efficiency and minimizing routing delay. In this article, a detailed comparative survey on energy-efficient clustering and routing protocols in WSN is presented. At first, energy-efficient clustering and routing protocols proposed for WSN in previous researches are studied in detail. After that, a comparative and state-of-the-art analysis is carried out to identify the limitations in those protocols and suggest a novel improvement on clustering and routing protocol with increased network lifetime and reduced energy consumption.